Discovery of Type II Inhibitors of TGFβ-Activated Kinase 1 (TAK1) and Mitogen-Activated Protein Kinase Kinase Kinase Kinase 2 (MAP4K2) - Tan, Li (J Med Chem, 2014)
[Image: see text] We developed a pharmacophore model for type II inhibitors that was used to guide the construction of a library of kinase inhibitors. Kinome-wide selectivity profiling of the library resulted in the identification of a series of 4-substituted 1H-pyrrolo[2,3-b]pyridines that exhibited potent inhibitory activity against two mitogen-activated protein kinases (MAPKs), TAK1 (MAP3K7) and MAP4K2, as well as pharmacologically well interrogated kinases such as p38α (MAPK14) and ABL. Further investigation of the structure–activity relationship (SAR) resulted in the identification of potent dual TAK1 and MAP4K2 inhibitors such as 1 (NG25) and 2 as well as MAP4K2 selective inhibitors such as 16 and 17. Some of these inhibitors possess good pharmacokinetic properties that will enable their use in pharmacological studies in vivo. A 2.4 Å cocrystal structure of TAK1 in complex with 1 confirms that the activation loop of TAK1 assumes the DFG-out conformation characteristic of type II inhibitors.